2022
DOI: 10.1108/yc-11-2021-1411
|View full text |Cite
|
Sign up to set email alerts
|

Why do young people do things for the environment? The effect of perceived values on pro-environmental behaviour

Abstract: Purpose This study aimed to develop an integrative model that comprehensively explores the antecedents of pro-environmental intentions in young people. The study follows customer value theory (CVT) and the theoretical framework of the theory of planned behaviour (TPB). Design/methodology/approach Data was obtained from a field survey of two secondary schools in Hong Kong. A total of 279 young people (age range: 10–12 years old; 53.8% males) were recruited to complete the survey. Smart-PLS 3 was used to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 96 publications
(113 reference statements)
1
8
0
Order By: Relevance
“…The entrepreneurial passion is an intense positive feeling (Cardon et al, 2013), this feeling is prone to carry out favorable outcomes. The pro-environmental behavior studies suggested that this behavior is particularly developed by risk perception, environmental values, social values and beliefs, individual own values and environmental problems (Ng and Cheung, 2022). COVID-19 crisis has affected proenvironmental behaviors to particular segments of different societies and in partial ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The entrepreneurial passion is an intense positive feeling (Cardon et al, 2013), this feeling is prone to carry out favorable outcomes. The pro-environmental behavior studies suggested that this behavior is particularly developed by risk perception, environmental values, social values and beliefs, individual own values and environmental problems (Ng and Cheung, 2022). COVID-19 crisis has affected proenvironmental behaviors to particular segments of different societies and in partial ways.…”
Section: Discussionmentioning
confidence: 99%
“…The proenvironmental behavior has been a focus of researchers where individuals seek protection of their environment. These are developed by risk perception, environmental values, social values and beliefs, individual own values, and environmental problems (Ng and Cheung, 2022). Their intentions to engage and other parameters are quite similar to ordinary entrepreneurs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This finding follows Geiger et al's (2019) study that environmental physics understanding is a core part of environmentally-friendly behavior. However, Ng and Cheung (2022) state that environmentally-friendly behavior will only occur after the individual experiences the influence of environmental physics understanding in his class so that the benefits of scientific reasoning are felt.…”
Section: Resultsmentioning
confidence: 99%
“…Second, Chin et al (2020) suggested that when the study aims to predict key target constructs in a research model, PLS-SEM is preferred. Third, PLS-SEM has been applied on previous marketing studies (Cheung et al , 2020; Ng and Cheung, 2022; Sudhir and Unnithan, 2019; Van Nguyen et al , 2021) to perform data analysis and it is appropriate to use in exploratory research with a combination of explanatory and prediction.…”
Section: Discussionmentioning
confidence: 99%